Abundance estimates of Southern Hemisphere Breeding Stock ‘D’ humpback whales from aerial and land-based surveys off Shark Bay, Western Australia, 2008 - Hedley, Sharon L.; Bannister, John L.; Dunlop, Rebecca A. (J. Cetacean Res. Manage., 2020)
Single platform aerial line transect and land-based surveys of Southern Hemisphere Breeding Stock ‘D’ humpback whales Megaptera novaeangliae were undertaken off Shark Bay, Western Australia to provide absolute abundance estimates of animals migrating northward along the western Australian coast. The aerial survey flew a total of 28 flights, of which 26 were completed successfully, from 24 June–19 August 2008. The landbased survey was undertaken from Cape Inscription, Dirk Hartog Island, Shark Bay, during the expected peak of the whales’ northward migration, from 8–20 July. During the first week of the land-based survey, some double count effort was undertaken to provide information on the numbers of pods missed from the land station. The assumed period of northward migration was 2 June–7 September. Estimated abundance of northwardmigrating whales during that time is 34,290 (95% CI: (27,340–53,350)), representing an annual rate of increase of 12.9% (CV = 0.20) since an estimate of 11,500 in 1999. This estimate is based on an estimate of relative abundance of surface-available whales of 10,840 (8,640–16,860), and an estimated g(0) of 0.32. There were considerable practical difficulties encountered during the land-based survey which reduced the effectiveness of the dual-survey approach for estimating g(0) for the aerial survey. Furthermore only about 15% of whales were estimated to be within the visual range of the land-based station. Alternative approaches for estimating g(0) from these data are therefore also presented, resulting in considerably higher estimates of around 0.6–0.7, and yielding a conservative abundance estimate of 17,810 (14,210–27,720).